2012
DOI: 10.1002/pola.25954
|View full text |Cite
|
Sign up to set email alerts
|

One‐pot, facile synthesis of well‐defined molecular brush copolymers by a tandem RAFT and ROMP, “Grafting‐through” strategy

Abstract: Two well‐defined brush copolymers, PNB‐g‐PMMA, were synthesized by a one‐pot, RAFT/ROMP, “grafting‐through” method, without intermediate steps of isolation or purification. The controlled dimensions of the brushes were verified by atomic force microscopy. This strategy significantly simplified the synthesis of brush copolymers when compared with conventional methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 63 publications
1
53
0
Order By: Relevance
“…[39][40][41][42][43] Following this seeded RAFT polymerization, a new block is introduced into the pre-prepared AB diblock copolymer nano-objects just as similarly as those in the graftthrough strategy to afford triblock copolymer nano-objects. 44 Recently, we have prepared ABA triblock copolymer corecorona particles following this seeded RAFT polymerization in the presence of the AB diblock copolymer nanoparticles. 42,43 It is found that the hydrodynamic diameter (D h ) of the ABA triblock copolymer core-corona particles increases with the polymerization degree (DP) of the newly introduced A block.…”
Section: Methodsmentioning
confidence: 99%
“…[39][40][41][42][43] Following this seeded RAFT polymerization, a new block is introduced into the pre-prepared AB diblock copolymer nano-objects just as similarly as those in the graftthrough strategy to afford triblock copolymer nano-objects. 44 Recently, we have prepared ABA triblock copolymer corecorona particles following this seeded RAFT polymerization in the presence of the AB diblock copolymer nanoparticles. 42,43 It is found that the hydrodynamic diameter (D h ) of the ABA triblock copolymer core-corona particles increases with the polymerization degree (DP) of the newly introduced A block.…”
Section: Methodsmentioning
confidence: 99%
“…As a result of the high reactivity of Ru catalysts, polymerization of MMs proceeds at a fast rate, even at low norbonenyl concentrations [157]. Furthermore, the ring strain of the norbonenyl functionality is released after polymerization, which provides an additional thermodynamic driving force for the graftingthrough polymerization process.…”
Section: Grafting-through Approachmentioning
confidence: 99%
“…ROMP also has demonstrated a wide functional group tolerance to produce well‐defined bottlebrush block copolymers with MMs carrying heteroatom functional groups through sequential ROMP 43–46. Well‐controlled MMs are needed for well‐defined bottlebrush polymers and they have been synthesized from a variety of techniques, which suppress side reactions of norbornene incorporation, such as reversible addition‐fragmentation chain transfer (RAFT) polymerization,47–49 atom transfer radical polymerization (ATRP),50–52 living anionic polymerization (LAP),53,54 ring‐opening polymerization (ROP),55 and other types of polymerizations 56,57. Thus, a wide library of potential MMs exist to create new bottlebrush block copolymers.…”
Section: Introductionmentioning
confidence: 99%